2007
DOI: 10.1158/0008-5472.can-06-1608
|View full text |Cite
|
Sign up to set email alerts
|

Merlin/Neurofibromatosis Type 2 Suppresses Growth by Inhibiting the Activation of Ras and Rac

Abstract: The small G-protein Ras is a tightly controlled regulator of cell fate. Prolonged or persistent arrest in the activated GTP-loaded state by mutation of Ras as in lung cancer or in a Ras-GTPase-activating protein as in neurofibromatosis type 1 promotes tumorigenesis. We now show that the tumorsuppressor protein merlin (mutated in neurofibromatosis type 2) also controls Ras activity. Systematic analysis of growth factor signaling located the step of merlin interference to the activation of Ras and Rac. Merlin in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
183
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 205 publications
(187 citation statements)
references
References 51 publications
3
183
0
1
Order By: Relevance
“…Merlin has been suggested to restrain tumor growth through inhibiting Rac and ERK activities (Shaw et al, 2001;Kissil et al, 2003;Okada et al, 2005;Morrison et al, 2007). To further substantiate a role of VprBP in Merlin function regulation, we tested whether Rac and ERK activities might be altered in VprBP-depleted cells.…”
Section: Vprbp Targets Merlin For Degradation J Huang and J Chenmentioning
confidence: 99%
“…Merlin has been suggested to restrain tumor growth through inhibiting Rac and ERK activities (Shaw et al, 2001;Kissil et al, 2003;Okada et al, 2005;Morrison et al, 2007). To further substantiate a role of VprBP in Merlin function regulation, we tested whether Rac and ERK activities might be altered in VprBP-depleted cells.…”
Section: Vprbp Targets Merlin For Degradation J Huang and J Chenmentioning
confidence: 99%
“…Schwannomas are the most frequent merlin-deficient tumours. Merlin belongs to the ERM (ezrin-radixin-moesin) family proteins (Rouleau et al, 1993;Bretscher et al, 2002) connecting actin cytoskeleton and membrane proteins and is crucial for the regulation of signalling pathways for maintaining normal cell function (Morrison et al, 2007;Okada et al, 2007;McClatchey and Fehon, 2009). Currently, there is no medical treatment for merlin-deficient tumours.…”
Section: Introductionmentioning
confidence: 99%
“…The volume calculation algorithm in OsiriX was used to obtain a threedimensional tumor volumetric measurement (mm 3 ) complex region, using the SC4-9 cell line. SC4-9 has become a standard model in NF2 research since it recapitulates signalling network signatures of human and mouse NF2 schwannomas [19,21,25,26], with high grafting efficiency when orthotopically injected into the sciatic nerves of immunodeficient NU/NU mice [34]. We found that the microsurgical approach successfully targeted the anatomic location where human VS predominantly arise and tumor development could be monitored by in vivo imaging.…”
Section: Discussionmentioning
confidence: 89%
“…The SC4 Schwann cell line was derived from adeno-Creinfected, spontaneously transformed Schwann cells isolated from adult Nf2 KO3/flox2 mouse sciatic nerve in the FVB/N background [18][19][20][21]. SC4 cells were transfected with a plasmid encoding a fusion EGFP-luciferase gene under the control of the CMV promoter, and stable cell clones were selected using cell sorting.…”
Section: Cell Linementioning
confidence: 99%
See 1 more Smart Citation